A Biblical Holistic Approach to Proverty - Jon Gunthorpe (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2019)
Historically, 'the poor' are those who are in need materially and so the way to care for them is to give financial or material assistance. While there has been some progress in the recent century, poverty alleviation still remains a major issue in our world. From a Biblical perspective poverty is one of the consequences of sin, but it is understood in a broader way than merely physical poverty. God works to reverse the results of sin and restore all things, which includes all forms of poverty. In the Old Testament the poor are most often discussed in economic terms, however there are also references to those in spiritual need. The primary principle was that the Israelites were to care for the poor among them, which reflected God's care for them. However, they often fail and are rebuked for exploiting the poor. In the New Testament poverty is discussed even more clearly in an holistic way: there are the materially poor, the socially poor, but all people are spiritually poor. Hence the way to care for the poor must address these different types of poverty. Of paramount importance is to help people out of spiritual poverty, for that has eternal consequences. However, it is also clear that Christians who properly understand God's grace to them, will respond by caring for others holistically. Such care was seen in the early NT church from congregations who were transformed to serve, as taught and modelled by Jesus. The ongoing challenge for Christian churches today is to continue to care for all varieties of the poor, enabling and empowering them to help themselves as Jesus' instructed.